ENHANCED PROPERTIES AND MULTIFACETED APPLICATIONS OF POLYMETHYL METHACRYLATE (PMMA) IN MODERN MEDICINE AND DENTISTRY - Alexandru Burcea; Andreea-Mariana Bănățeanu; Cristian-Viorel Poalelungi; Alexandru Burcea; Norina Forna; Cristian Niky Cumpătă (Romanian Journal of Oral Rehabilitation)
Polymethyl methacrylate (PMMA) is a versatile polymer widely used in medical, dental, and cosmetic applications due to its impressive transparency, biocompatibility, and stability against environmental factors. This review examines recent advancements in PMMA composites aimed at enhancing biocompatibility and reducing toxicity, particularly in medical applications. Innovations include the integration of nanoparticles to improve mechanical properties and reduce bacterial colonization, as well as the development of novel composites that exhibit increased durability and enhanced cellular interactions. Additionally, the review discusses the implications of these advancements for medical and dental practices, emphasizing the importance of material selection in clinical outcomes. It also highlights the ongoing challenges and potential health risks associated with PMMA, particularly concerning its interaction with biological systems. The integration of cutting-edge research and technology in PMMA composites is crucial for developing safer, more effective medical devices and interventions, ultimately leading to better patient outcomes and broader applications in healthcare.